Transcriptome and metabolome analysis reveal the lip color variation in Cymbidium floribundum - Shanhu Ma; Mengjie Wang; Peng Li; Liting Guo; Longwei Xiong; Yang Tian; Jinjin Li; Siren Lan; Zhongjian Liu; Ye Ai (Ornamental Plant Research, 2024)
Cymbidium floribundum is an ornamental plant with showy and colorful flowers. The color of its lip changes significantly after pollination. However, the mechanism of lip coloration remains unclear. In this study, the mechanism underlying lip color change in C. floribundum was investigated before and after pollination. Metabolome analysis detected 61 flavonoids in the lip, including 24 flavonoids, 13 flavonols, nine flavonoid carbonosides, eight anthocyanins, three flavanols, two isoflavones, one chalcone, and one dihydroflavone. Accumulation of peonidin 3-O-glucoside chloride, cyanin chloride, and cyanidin 3-O-malonylhexoside after pollination may be the key factors contributing to the change in lip color. Furthermore, transcriptome analysis identified 43 genes related to the anthocyanin biosynthesis pathway (ABP). Phylogenetic and co-expression analysis indicated that CfMYB1, CfMYB3, and CfMYB4 may be involved in the regulation of anthocyanin biosynthesis in the lips. Subcellular localization results showed that CfMYB1 was located in the nucleus, while CfMYB3 and CfMYB4 were located in the nucleus and cytoplasm. Further functional analysis verified that CfMYB1 could activate ABP genes and promote the synthesis and accumulation of anthocyanin, which may be the main transcription factors leading to the change of lip color in C. floribundum after pollination. These findings provide insight into the anthocyanin accumulation and coloration mechanisms during C. floribundum flower development. The results provide genetic resources and a theoretical basis for the improvement and breeding of flower color in C. floribundum.